Gastric Dilation due to a Neuroleptic Agent in an Elderly Patient: A Case Report. (5th August 2014) - Parent, V.; Popitean, L.; Loctin, A.; Camus, A.; Manckoundia, P.
Abstract : Neuroleptics may cause side effects, some of which are little known. We describe here a case of gastric dilation related to treatment with a neuroleptic in an elderly man. To our knowledge, such a case has never been reported in the literature. A 76-year-old man, living in a nursing home, was hospitalized for general weakness and abdominal pain. He had dementia with behavioral disorders treated with cyamemazine, a sedative and anxiolytic neuroleptic. Given a clinical suspicion of intestinal occlusion, an abdominopelvic computerized tomography scan was performed before the patient was admitted to our hospital. This computerized tomography scan did not show intestinal occlusion and there was no mention of gastric dilation in the computerized tomography scan report. Thus, acute gastroenteritis was suspected. The usual medications were stopped and symptomatic treatment for gastroenteritis was started. Quickly, his clinical state and biological parameters returned to normal and his usual treatment, including cyamemazine, was started again. The next day, the digestive symptoms, except for obstipation, reappeared. The abdominal X-ray showed gastric dilation without intestinal occlusion. The neuroleptic was stopped again and symptoms vanished the next day. This report underlines all of the necessary precautions and surveillance around drug prescription, especially in elderly persons.